Superconductivity and Its Enhancement in Polycyclic Aromatic Hydrocarbons - Zhong, Guo-Hua; Chen, Xiao-Jia; Lin, Hai-Qing (Frontiers in Physics, 2019)
The discovery of superconductivity above 30 K in aromatic hydrocarbons in the past years has been an exciting event in condensed matter physics, chemistry, and materials. Superconductivity was realized by simply introducing electrons in the network made by carbon and hydrogen - the two components for organic systems. However, the accurate amount of doped electrons and their positions have not been established experimentally. No agreement has been reached for the mechanism of their superconductivity. Here, the first principles theory with the combination of electron correlations is used to address these problems. Our calculations show that both the single-ring compound (benzene) and the two-benzene rings compound (naphthalene) are superconductors with transition temperatures (Tc’s) of 6.2 K and 5.8 K respectively after upon doing of potassium. By examining the existing experimental data carefully, we find that there exists a unique superconducting phase with Tc in the range of 5 - 7 K range for all aromatic hydrocarbons. The almost constant low density of states at Fermi level with about two electrons doping accounts for this unified phase. The high density of states at Fermi level upon three-electron doping seems responsible for the high-Tc phase in these hydrocarbons with long benzene rings. Meanwhile, the electronic correlations also increase with increasing the number of benzene rings. These findings offer clues to the understanding of the superconductivity as well as to the search of new superconductors in this family.